EXPERIMENTAL ABIOTIC SYNTHESIS OF METHANOL IN SEAFLOOR HYDROTHERMAL SYSTEMS DURING DIKING EVENTS - Voglesonger K.M.; Holloway J.R.; Dunn E.E.; Dalla-Betta P.J.; O'Day P.A. (My University, 2001)
The abiotic synthesis of organic compounds in seafloor hydrothermal systems is one mechanism through which the subsurface environment could be supplied with reduced carbon. A flow-through, fixed-bed laboratory reactor vessel, the Catalytic Reactor Vessel (CRV) system, has been developed to investigate mineral-surface promoted organic synthesis at temperatures up to 400°C and pressures up to 30 MPa, conditions relevant to seafloor hydrothermal systems. Here we present evidence that metastable methanol can be directly synthesized from a gas-rich CO2-H2-H2O mixture in the presence of a mineral substrate. Experiments have been performed without a substrate, with quartz, and with a mixture of quartz and magnetite. Temperatures and pressures in the experiments ranged from 200°C to 350°C and from 15 to 18 MPa, respectively. Maximum conversion of 5.8x10-4% CO2 to CH3OH per hour was measured using a mixture of magnetite and quartz in the reactor. After passivation of the stainless steel reactor vessel, experiments demonstrate that methanol is formed at temperatures up to 350°C in the presence of magnetite, and that the formation rate decreases over time. The experiments also show a loss of surface reactivity at 310°C and a regeneration of surface reactivity with increased temperature up to 350°C. Concentrations of CO2 and H2 used in the experiments simulate periodic, localized and dynamic conditions occurring within the seafloor during and immediately following magmatic diking events. High concentrations of CO2 and H2 may be generated by dike injection accompanied by exsolution of CO2 and reaction of dissolved H2O with FeO in the magma to form H2. The experiments described here examine how the ephemeral formation of an H2-CO2-rich vapor phase within seafloor hydrothermal systems may supply reactants for abiotic organic synthesis reactions. These experiments show that the presence of specific minerals can promote the abiotic synthesis of simple organic molecules from common inorganic reactants such H2O, CO2 and H2 under geologically realistic conditions.
Keywords: HYDROTHERMAL VENTS; ORGANIC SYNTHESIS; MID-OCEAN RIDGES; CATALYSIS